2022
DOI: 10.1021/jacs.2c00094
|View full text |Cite
|
Sign up to set email alerts
|

A Fluorogenic ONOO-Triggered Carbon Monoxide Donor for Mitigating Brain Ischemic Damage

Abstract: Ischemia–reperfusion (I/R) injuries are from the secondary radicals of ONOO–. Direct radical scavenging is difficult because of their high reactivity. ONOO– is longer-lived than the radicals in the biological milieu. Scavenging ONOO– suppresses radical generation preventively. CO is neuroprotective during ischemia. With the scaffold of carbon-caged xanthene, we designed an OONO–-triggered CO donor (PCOD585). Notably, PCOD585 exhibited a concomitant fluorescence turn-on upon ONOO–detection, facilitating microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 46 publications
0
27
0
1
Order By: Relevance
“…Fluorescence imaging has become a robust tool to directly image and monitor vital biomolecules and their associated processes. Various fluorescent probes with blue to near-infrared emissions have been elegantly synthesized for LD dynamic imaging. However, most of these LD probes suffer from low resolution (>200 nm) . To overcome this bottleneck, super-resolution imaging techniques have become an indispensable approach to accurately visualize nanoscale structures below 200 nm. Indeed, a few research groups successfully constructed new LD-specific fluorescent probes for super-resolution imaging using structured illumination microscopy (SIM) and stimulated emission depletion (STED) microscopy. Interesting imaging results of nano-sized cytosolic LDs with improved higher resolution over traditional confocal laser scanning microscopy (CLSM) have been acquired.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence imaging has become a robust tool to directly image and monitor vital biomolecules and their associated processes. Various fluorescent probes with blue to near-infrared emissions have been elegantly synthesized for LD dynamic imaging. However, most of these LD probes suffer from low resolution (>200 nm) . To overcome this bottleneck, super-resolution imaging techniques have become an indispensable approach to accurately visualize nanoscale structures below 200 nm. Indeed, a few research groups successfully constructed new LD-specific fluorescent probes for super-resolution imaging using structured illumination microscopy (SIM) and stimulated emission depletion (STED) microscopy. Interesting imaging results of nano-sized cytosolic LDs with improved higher resolution over traditional confocal laser scanning microscopy (CLSM) have been acquired.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it's well‐known that a large portion of intracellular ONOO − was spawned from the reaction of NO and O 2 −. , [21] thus, the inhibition of the ONOO − generation could be effective through reducing NO or O 2 −. concentration.…”
Section: Resultsmentioning
confidence: 99%
“…[20] As shown in Figure 4B and 4D, compared with the control group, a strong red fluorescence signal was captured in cells treated with such stimulants, denoting an increasing intracellular ONOO À concentration. Moreover, it's well-known that a large portion of intracellular ONOO À was spawned from the reaction of NO and O 2 À * , [21] thus, the inhibition of the ONOO À generation could be effective through reducing NO or O 2 À * concentration. To achieve this goal, cells which pre-treated with stimulants were further treated with Nacetyl cysteine (NAC, an antioxidant), aminoguanidine (AG, a frequently used inhibitor of NO synthetase), and 2,2,6,6-tetramethyl-piperidinooxy (TEMPO, an O 2 À * scavenger), [22] separately.…”
Section: Methodsmentioning
confidence: 99%
“…This may be related to the oxidative/nitrosative stress reaction after reperfusion, in which free radicals play an important role ( Sun et al, 2018 ). An animal experiment in 2022 showed that preventive inhibition of free radical production could reduce cerebral edema in reperfused MCAO rats ( Xing et al, 2022 ). Excessive nitric oxide levels after reperfusion can affect activation of the MMP pathway and the distribution of tight junctions, leading to destruction of the BBB and cerebral edema aggravation ( Sun et al, 2018 ).…”
Section: Factors Associated With the Formation Of Cerebral Edemamentioning
confidence: 99%